Mulheres e agroecologia: possibilidades para sustentabilidade local da Comunidade Bom Jesus, Assentamento Maceió, Itapipoca-Ce - Camurça, Andréa Machado (2013)
New perspectives in relation to the rural and agriculture has gained prominence in the face of crises (energy, food, environmental, economic and others) caused by the expansion of the logic of capital. So agricultures styles based on principles of agroecology gain visibility to seek the preservation of biodiversity, enhancement of more horizontal relations between "human-nature" and between them, ensuring the sovereignty and food security and local sustainability. Therefore, this study aims to understand the action of women in the management of activities in the backyards of the Community Bom Jesus, Maceio rural settlement, Itapipoca-CE. We used method with a critical feminist approach in conjunction with the peasantry elements. Methods, we chose to case study associated with participant observation techniques and interviews. The instruments were field diary, semi-structured script, camera and recorder. The results indicate that women in the practice of peasant agriculture developed in the yards has been mainly responsible for the preservation of biodiversity, management and varied techniques, crops associated with small livestock, the extraction and processing of food for family consumption and for playback. Backyards practiced since the dawn of agriculture constitute one way and know-how of women in agriculture that are indicating elements (ecological, social, economic and cultural) important to agroecology, such as biodiversity conservation, multiple handlings food production without pesticides and without fertilizers. The actual dialogue of women with the principles of agroecology, experienced in the yard, are improvers of new meanings to society.